Manajemen Risiko : Risiko Lingkungan Akibat Terbengkalainya Pekerjaan Proyek Jembatan Siak 4 Kota Pekanbaru - Prama Widayat (Jayapangus Press, 2018)
The development of an urban infrastructure should be well planned both from the financial and non-financial side so as not to cause problems in the future which may interfere with the work, but not with the construction of siak bridge 4 Pekanbaru City which started in 2009 and stopped working in 2012, end of year 2017 just started again construction work and that too new work to build block pavling under the bridge instead of continuing the main work of connecting the two sides of the bridge. By conducting SWOT analysis, it is found that the dominant environmental risk is the policy of Riau provincial government using siak bridge construction budget 4 for PON activities in 2012, so that the construction of the bridge becomes dormant for 5 years (2012-2017), then the access of citizens to the city center becomes blocked by a bridge that is not finished.